Media Optimization for Serratiopeptidase by Statistical Approach followed by Isolation and Product Purification - Vandana Gupte, R.R.Patil, Umesh Luthra, Nishtha K.Singh , Vrushali Bhosle , (International Journal of Scientific Research and Management (IJSRM), 2014)
Serratiopeptidase is a potent anti-inflammatory , proteolytic enzyme isolated from Serratia marcescens. The main goal of this study was to optimize the medium to increase the productivity of serratiopeptidase, which was carried out by using Plackett-Burman design for screening of nine medium components out of which the concentration of three significant factors (soya oil, soya flour and casein) were narrowed down for CCD and RSM analysis to understand the mutual interactions between selected factors.Maximum productivity of i.e.15,000 SPU/ml/ml was achieved by applying statistical approach.